2019
DOI: 10.3389/fimmu.2019.00624
|View full text |Cite
|
Sign up to set email alerts
|

Donor Allospecific CD44high Central Memory T Cells Have Decreased Ability to Mediate Graft-vs.-Host Disease

Abstract: Data from both animal models and humans have demonstrated that effector memory T cells (T EM ) and central memory T cells (T CM ) from unprimed donors have decreased ability to induce graft-vs-host disease (GVHD). Allospecific T EM from primed donors do not mediate GVHD. However, the potential of alloreactive T CM to induce GVHD is not clear. In this study, we sought to answer this question using a novel GVHD model indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…112 The latter defect in memory T cells seems to involve enhanced AICD and exhaustion/ anergy. 113,114 It is therefore intriguing to consider that this may reflect a differential sensitivity of memory T cells to recipient DC-invoked AICD, and this should be further investigated. In humans, mHA-reactive CD8 T cells exist with high frequency, primarily in the naïve T-cell subset.…”
Section: Antigen Presentation Requirements For Gvl Effectsmentioning
confidence: 99%
“…112 The latter defect in memory T cells seems to involve enhanced AICD and exhaustion/ anergy. 113,114 It is therefore intriguing to consider that this may reflect a differential sensitivity of memory T cells to recipient DC-invoked AICD, and this should be further investigated. In humans, mHA-reactive CD8 T cells exist with high frequency, primarily in the naïve T-cell subset.…”
Section: Antigen Presentation Requirements For Gvl Effectsmentioning
confidence: 99%
“…Several lines of evidence suggested that CD44 hi and CD122 hi T cells do not induce GVHD [27][28][29]. Our data showed that a high proportion of CD8 + T cells from Cat-Tg mice are CD44 hi and CD122 hi and express higher levels of Eomes (IMP phenotype) [19].…”
Section: Discussionmentioning
confidence: 49%
“…Several lines of evidence suggested that CD44 hi and CD122 hi T cells do not induce GVHD (36)(37)(38). Our data showed that a high proportion of CD8 + T cells from Cat-Tg mice are CD44 hi and CD122 hi and express higher levels of Eomes (IMP phenotype) (29).…”
Section: Discussionmentioning
confidence: 49%